OnabotulinumtoxinA Is an Effective Treatment for Chronic Migraine in Patients With Comorbid Fibromyalgia - Sastre Real, María; Díaz de Terán, Javier (Frontiers in Neurology, 2020)
Introduction Fibromyalgia (FM) is a frequent comorbidity in patients with chronic migraine (CM). PREEMPT trials, that demonstrated the efficacy of OnabotulinumtoxinA (OnabotA) on CM, excluded patients with FM. Our aim was to evaluate the effectiveness of OnabotA in a series of patients with CM and FM. Methods We analyzed patients with a previous diagnosis of CM and FM who had received sessions of OnabotA quarterly between January 2014 and January 2020 in a specialized Headache Clinic. Primary endpoint was the reduction in moderate to severe headache days at 3, 6, 9 and 12 months. Results Data were collected from 31 patients with CM and FM that received OnabotA (100% females). Mean age at first procedure was 50.2± 11.3 years. Depression (93.5%), other central sensitization syndromes (irritable bowel syndrome, interstitial cystitis, multiple chemical sensitivity, endometriosis and chronic fatigue syndrome) (48.4%) and medication overuse headache (90.3%) were frequent comorbidities. 48.4 % of patients had failed ≥ 3 preventives previously. The percentage of patients who achieved ≥30% and ≥50% moderate-severe headache reduction at third month was 65.4% and 48.2%, respectively. 23 patients completed 4 cycles of treatment, with 13.4 fewer headache days per month than at baseline (p<0.001). By 1 year, 69.5% had ≥50% reduction of headache frequency and 39.1% had a ≥75% reduction. In 4 cases (21%) OnabotA was interrupted due to a lack of response. Only mild adverse effects were recorded. Conclusion OnabotA is an effective treatment for CM in patients with FM.